An invasive strategy is associated with improved short- and long-term outcomes in acute myocardial infarction independently of frailty status and GRACE score: a nationwide analysis of 12144 episodes. (25th November 2020) - Pessoa Amorim, G; Santos-Ferreira, D; Azul Freitas, A; Santos, H; Belo, A; Gavina, C; Terenas Baptista, R; Monteiro, S
Abstract: Introduction: Frailty is common among patients presenting with acute myocardial infarction (MI), who have conflicting risks regarding benefits and harms of invasive procedures. Purpose: To assess the clinical management and prognostic impact of invasive procedures in frail MI patients in a real-world scenario. Methods: We analysed 5422 episodes of ST-elevation MI (STEMI) and 6692 of Non-ST-elevation MI (NSTEMI) recorded from 2010–2019 in a nationwide registry. A validated deficit-accumulation model was used to create a frailty index (FI), comprising 22 features [BMI >25kg/m 2, myocardial infarction, angina, heart failure, percutaneous coronary intervention (PCI), coronary artery bypass graft surgery (CABG), valvular disease, bleeding, pacemaker/implantable cardioverter defibrillator, chronic kidney disease (creatinine >2.0mg/dL), dialysis/renal transplant, stroke/transient ischaemic attack, diabetes, hypertension, dyslipidaemia, smoking, peripheral vascular disease, dementia, chronic lung disease, malignancy, polymedication (>3 cardiovascular drugs), admission haemoglobin <10g/dL; not including age]. Episodes with missing data on any FI parameter were not included. Frailty was initially defined as FI>0.25 (i.e. ≥6 features). Results: Overall, 511 (9.4%) STEMI and 1763 (26.4%) NSTEMI patients were considered frail. Angiography, PCI and CABG were less frequently performed in frail patients (p<0.001). Delayed angiography (>72h) was more common among NSTEMI frail patients (p<0.001), and radial access was less commonly used overall (p<0.001). Guideline-recommended in-hospital medical therapy, including aspirin (NSTEMI), dual-antiplatelet therapy (STEMI/NSTEMI), heparin/heparin-related agents (NSTEMI), beta-blockers (STEMI) and ACEIs/ARBs (STEMI), was less commonly used in frail patients; discharge medical therapy exhibited similar patterns. Frail patients had longer hospital stay and increased in-hospital all-cause and cardiovascular (CV) mortality, as well as 1-year all-cause and CV hospitalization and all-cause mortality (p<0.001). Using receiver-operator-characteristics curve analysis, FI cutoffs of 0.11 (STEMI) and 0.20 (NSTEMI) yielded the best accuracy to predict 1-year all-cause mortality (area under the curve: 0.629 and 0.702 respectively, p<0.001) – these cutoffs were subsequently used to define frailty. Although frailty attenuated in-hospital risk reductions from angiography (STEMI/NSTEMI) and PCI (NSTEMI only) (Wald test p<0.05), their 1-year prognostic benefit remained unaffected (Wald test p>0.05). Angiography and PCI were associated with improved in-hospital and 1-year outcomes, independently of frailty status or GRACE score (p<0.001). Conclusion: Frail MI patients are less commonly offered standard therapy; however, angiography and PCI were associated with short- and long-term prognostic benefits regardless of frailty status or GRACE score. Increased adherence to current recommendations might improve post-MI outcomes in frail patients. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Portuguese Society of Cardiology